Gambaran Pengetahuan Tanda dan Gejala serta Sikap Remaja Putri Tentang Anemia di SMP N 9 Kota Jambi Tahun 2024 - Nabilla, Shalsya Nur; Indrawati, Iin; Hidayat, Muhammad; Fatmawati, Tina Yuli (3031-8572, 2024)
Anaemia is a condition in which haemoglobin levels are lower than normal. According to the Indonesian Ministry of Health (2018), the prevalence of anaemia among adolescents in Indonesia is 32%. Knowledge is a very important area in shaping a person's actions or attitudes, because actions based on knowledge will be better than behaviour that is not based on knowledge. The purpose of this study was to determine the knowledge of signs and symptoms and attitudes towards anaemia among adolescent girls in SMP N 9 Jambi City. This research is a quantitative study using a descriptive research design. The population of this study was 225 adolescent girls of SMP N 9 Jambi City with a sample of 52 adolescent girls of SMP N 9 Jambi City. The sampling technique used was proportional random sampling technique. Data collection technique used questionnaire. Data analysis in this study used univariate analysis which then the results will show the frequency distribution of the variables studied, namely knowledge of signs and symptoms and attitudes. The results showed that the percentage of poor knowledge about the signs and symptoms of anaemia was (84.6%), good knowledge was (15.4%). Attitude is not good about anaemia as much as (63.5%), good attitude (36.5%). In this study, it can be concluded that the knowledge and attitude of adolescent girls are still not good about anaemia